2020
DOI: 10.1038/s41598-020-62057-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis uncovers the gene expression profile of salt-stressed potato (Solanum tuberosum L.)

Abstract: potato (Solanum tuberosum L.) is an important staple food worldwide. However, its growth has been heavily suppressed by salt stress. The molecular mechanisms of salt tolerance in potato remain unclear. It has been shown that the tetraploid potato Longshu No. 5 is a salt-tolerant genotype. Therefore, in this study we conducted research to identify salt stress response genes in Longshu No. 5 using a NaCl treatment and time-course RNA sequencing. The total number of differentially expressed genes (DEGs) in respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 110 publications
(113 reference statements)
3
25
0
Order By: Relevance
“…The ectopic expression of the barley [30], wheat [31,32], and rice [33] ERF genes also enhanced tolerance to salt stress. Consistent with our results, recent transcriptomic studies in cotton [34] and potato [35] plants revealed the induction of a high proportion of ERFs in response to salt stress, suggesting the essential role of ERFs in salt response mechanisms in plants. Despite its significance, with few exceptions [36,37], there is not much information available about the role of ERF TFs in cucurbits.…”
Section: Differentially Expressed Transcription Factors (Tf) In Response To Salinity Stresssupporting
confidence: 92%
“…The ectopic expression of the barley [30], wheat [31,32], and rice [33] ERF genes also enhanced tolerance to salt stress. Consistent with our results, recent transcriptomic studies in cotton [34] and potato [35] plants revealed the induction of a high proportion of ERFs in response to salt stress, suggesting the essential role of ERFs in salt response mechanisms in plants. Despite its significance, with few exceptions [36,37], there is not much information available about the role of ERF TFs in cucurbits.…”
Section: Differentially Expressed Transcription Factors (Tf) In Response To Salinity Stresssupporting
confidence: 92%
“…This transporter has been proposed to play a dual role, act as the antiporter, and play a role in cellular processes, such as ionic homeostasis, stomatal regulation, and maintenance of cell turgor [76]. The other most important Na + /H + antiporter present on the plasma membrane, which plays a significant role in salinity tolerance, is SOS1 (Salt Overly Sensitive 1) in potato was identified by transcriptome analysis [80]. The conceptual model for ion homeostasis is explained in Figure 2.…”
Section: Ion Homeostasismentioning
confidence: 99%
“…However, the transcriptional responses of P. indica to high salt stress have yet to be delineated. The recent advances in high-throughput sequencing technologies, for example, RNA-Seq and the genome sequencing of P. indica have helped tremendously to provide a global view of the P. indica transcriptome 31 , 33 .…”
Section: Discussionmentioning
confidence: 99%